Yes, peut-être de Marguerite Duras : réécriture de l’histoire - Ana Fernandes (Carnets)
May 68 in France became an important cultural moment in the history of France and it is often present in current political debates. We propose that the criticism of French society during the events of May and June 1968 existed already before this time and can be seen in the literature and in creative expression of that time in the piece Yes, peut-être of Marguerite Duras. It expresses a deep discontent regarding society where she lives and his work to imagine the consequences of Western ideals took to their limits. Oblivion and re-writing of the history of the events of May 1968 led to a modern failure to understand these events. The oblivion of history with his recreation elements are present in the work of Duras, in creating new and hybrid versions Western familiar stories. Remember history is an important task and that requires revisionist views. The story must be reviewed holistically and established, based on a variety of perspectives that can incorporate various points of view.